A Research Study on the Teleworking in Engineering Sectors in UAE - AL RAYSSI, MANEA (2022)
Organization measures its success by its employee’s performance. It is one of the most important measurements tool to indicate the efficiency and effectiveness of the corporate system performance. Employees are the valuable resources in any departments, projects, product and service. COVID pandemic has forced the world to make new arrangement (which is remotely working) from the workplaces. Engineering and industrial sector forced their employees to implement this work arrangement, which led to disturbing some organization performance. The purpose of this study is to examine how level of autonomy, feedback quality, communication process, Work-Life Interference and communication tools, affected the employee performance in the engineering and industrial sector during remotely working arrangement in COVID pandemic.